Analysis of an Integrated 8-Channel Tx/Rx Body Array for Use as a Body Coil in 7-Tesla MRI - Orzada, Stephan; Bitz, Andreas K.; Johst, Sören; Gratz, Marcel; Völker, Maximilian N.; Kraff, Oliver; Abuelhaija, Ashraf; Fiedler, Thomas M.; Solbach, Klaus; Quick, Harald H.; Ladd, Mark E. (Frontiers in Physics, 2017)
Object In this work an 8-channel array integrated into the gap between the gradient coil and bore liner of a 7-Tesla whole-body magnet is presented that would allow a workflow closer to that of systems at lower magnetic fields that have a built-in body coil; this integrated coil is compared to a local 8-channel array built from identical elements placed directly on the patient. Materials and Methods SAR efficiency and the homogeneity of the right-rotating B1 field component (B_1^+) are investigated numerically and compared to the local array. Power efficiency measurements are performed in the MRI System. First in vivo gradient echo images are acquired with the integrated array. Results While the remote array shows a slightly better performance in terms of B_1^+ homogeneity, the power efficiency and the SAR efficiency are inferior to those of the local array: the transmit voltage has to be increased by a factor of 3.15 to achieve equal flip angles in a central axial slice. The g-factor calculations show a better parallel imaging g-factor for the local array. The field of view of the integrated array is larger than that of the local array. First in vivo images with the integrated array look subjectively promising. Conclusion Although some RF performance parameters of the integrated array are inferior to a tight-fitting local array, these disadvantages might be compensated by the use of amplifiers with higher power and the use of local receive arrays. In addition, the distant placement provides the potential to include more elements in the array design.